Penguatan Produk UMKM Rayszava (Mijun) Tenant Inkubator Unit Bisnis LPPM Unnes - Hidayah, Isti; Prajanti, Sucihatiningsih Dian Wisika; Wiyanto, Wiyanto; Mujaki, Ahmad (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
The urgency of this community service partnership is that strengthening MSME products and management is a strategic step toward increasing competitiveness, business sustainability, and the preservation of Indonesia's cultural heritage. In an increasingly competitive market, many traditional spice-based food and beverage MSMEs face challenges such as limited product variety due to limited innovation, low selling prices, limited public knowledge and farmer empowerment, and financial accounting and marketing issues. The problems faced by Rayszava (Mijun) spice-processed food and beverage MSME tenants include insufficient production quantities, a lack of understanding of financial accounting, and marketing strategies that make it difficult to compete in both local and global markets. The solutions to overcome these problems include applying appropriate technology to increase quantity and maintain product quality, as well as offering product variety in spice mixture levels. This supports achieving the SDGs (Sustainable Development Goals), namely “Good Health and Well-being” and “Decent Work and Economic Growth”. The implementation methods applied include 1) Socialization, 2) Training, 3) Assistance, 4) Evaluation, and 5) Sustainability. The output targets achieved include the use of crystallization machines to optimize production and improve time and energy efficiency.